2016
DOI: 10.1111/nep.12645
|View full text |Cite
|
Sign up to set email alerts
|

Changes in hydration following haemodialysis estimated with bioimpedance spectroscopy

Abstract: Although more convenient to make bioimpedance measurements of hydration status pre-dialysis, we did not find that changes in OH post-dialysis mirrored the changes in measured weight. As such, single pre-dialysis bioimpedance measurements of hydration status may not accurately predict post-dialysis hydration status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
0
14
1
1
Order By: Relevance
“…Data collected during a study to compare distribution of fluid in haemodialysis patients and normal controls allowed us to reproduce the study recently reported by El‐Kateb and Davenport . BCM measurements were made on 47 HD patients, 60% men, mean age 60 ± 16 years, before and after dialysis.…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…Data collected during a study to compare distribution of fluid in haemodialysis patients and normal controls allowed us to reproduce the study recently reported by El‐Kateb and Davenport . BCM measurements were made on 47 HD patients, 60% men, mean age 60 ± 16 years, before and after dialysis.…”
mentioning
confidence: 59%
“…BCM measurements were made on 47 HD patients, 60% men, mean age 60 ± 16 years, before and after dialysis. In contrast to El‐Kateb and Davenport, there was a strong correlation between the fall in fluid overload (‘overhydration’, OH) from 1.5 ± 1.5 to −0.4 ± 1.5 L and the fall in body weight from 81.6 ± 22.6 to 80.0 ± 22.6 kg (Pearson r = 0.65, p < 0.0001).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike with some other BIS devices, the electrodes remained in place during the dialysis session [29], and no electrode had to be replaced, thereby eliminating error due to changes in electrode position.…”
Section: Discussionmentioning
confidence: 99%
“…There were several methods to measure lean muscle mass and fat mass, such as dual‐energy X‐ray absorptiometry (DEXA) and bioimpedance analysis (BIA). However, these methods were not available worldwide and might require repeat measurements …”
Section: Introductionmentioning
confidence: 99%